2011
DOI: 10.1186/1471-2458-11-32
|View full text |Cite
|
Sign up to set email alerts
|

Do patients with recurrent episodes of campylobacteriosis differ from those with a single disease event?

Abstract: BackgroundAlthough Campylobacter is the leading cause of reported bacterial gastro-enteritis in industrialized countries, little is known on its recurrence. The objective of this study is to describe the risk and the patient characteristics of recurrent episodes of human campylobacteriosis reported in Quebec.MethodsLaboratory-confirmed cases of campylobacteriosis reported in the province of Quebec, Canada, through ongoing surveillance between 1996 and 2006 were analyzed. The risk of having a recurrent episode … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 31 publications
0
20
0
Order By: Relevance
“…We are not aware of previous evidence from observational studies for such strong clustering effects in adult age groups. In an analysis of surveillance data on laboratory-confirmed campylobacteriosis in Québec, Canada, Arsenault et al found that, over a period of 11 years, a second episode of Campylobacter IID was more likely to be reported among those aged 15 years and above compared with children under 5 years [15]. …”
Section: Discussionmentioning
confidence: 99%
“…We are not aware of previous evidence from observational studies for such strong clustering effects in adult age groups. In an analysis of surveillance data on laboratory-confirmed campylobacteriosis in Québec, Canada, Arsenault et al found that, over a period of 11 years, a second episode of Campylobacter IID was more likely to be reported among those aged 15 years and above compared with children under 5 years [15]. …”
Section: Discussionmentioning
confidence: 99%
“…Although core-genome (as described by MLST) is not necessarily related to antigens, and cross-protection is expected to develop for strains sharing similar antigenic properties, the higher risk of campylobacteriosis in travellers does not appear to be limited just to higher levels of exposure in developing countries, but also to the possible presence of 'new' Campylobacter strains, endemic in the different regions to which travellers have rarely been exposed before [14]. It follows that, probabilistically, these new strains are more likely to be associated with regionally untested antigens than widespread strains, and acquired protection may be ineffective when exposed to uncommon strains, as evidenced by a Canadian study [15].…”
Section: Introductionmentioning
confidence: 99%
“…The disease can have a protracted course but can also present as an acute and potentially life-threatening infection (5), as occurred in one of our patients. Certain conditions, such as chronic intestinal diseases, diabetes, liver disease, metastatic cancers, and AIDS, as well as hypogammaglobulinemia and the use of proton-pump inhibitors, may be associated with a higher risk of acquiring the infection (9). Humoral immunity plays a crucial role against Campylobacter spp., and recurrent infection has been reported in patients with conditions associated with impaired humoral immunity (5), as was the case of both our patients.…”
Section: Ampylobacter Jejuni and Campylobacter Coli Among Othermentioning
confidence: 99%